A Short History of Film - Dixon, Wheeler W., 1950- (Book collections on Project MUSE., 2008)
The history of international cinema is now available in a concise, conveniently sized, and affordable volume. Succinct yet comprehensive, A Short History of Film provides an accessible overview of the major movements, directors, studios, and genres from the 1880s to the present. More than 250 rare stills and illustrations accompany the text, bringing readers face to face with many of the key players and films that have marked the industry. Beginning with precursors of what we call moving pictures, Wheeler Winston Dixon and Gwendolyn Audrey Foster lead the reader on a fast-paced tour through th.